Akibat Hukum Terjadinya Wanprestasi Dalam Perjanjian Kerja Tanpa Adanya Jaminan - Nur Sharky, Yoliandri; Djajaputra, Gunawan (Universitas Ekasakti, 2024)
Default is non-fulfillment of an obligation or obligation carried out by parties who are mutually binding. In the case of a cooperation agreement, it is often one of the parties that does not carry out the achievements as agreed. Default is carried out through several stages, namely a warning or subpoena which if there is no response then it can go to the court stage. In the case raised in the Supreme Court Decision Number 1386K/PDT/2020, that the Abdurrab Foundation committed an act of default in an agreement with PT Karya Metropolitan Utama because the Foundation did not fulfill its achievements and broke a promise. The research method used in this study uses normative juridical methods using secondary data. Then the results of the study stated that the judge's decision in granting part of the plaintiff's lawsuit was in accordance with the law and there was no deviation in deciding a case.